HIV response financing challenges in Sub-Saharan Africa: barriers to achieving the 95-95-95 UNAIDS targets - Kulohoma, Benard W.; Wesonga, Colette A. (Frontiers in Public Health, 2025)
Sub-Saharan Africa (SSA) faces a critical HIV financing crisis that threatens the 2030 goal of ending HIV as a public health threat. Despite accounting for 77% of weekly global new HIV infections, occurring among adolescent girls and young women, only 1% of annual global health spending is available for SSA, where 16% of the world’s population resides. This disparity undermines progress toward the UNAIDS 95-95-95targets for HIV diagnosis, treatment access, and viral suppression. Multiple converging health financing gaps exacerbate this crisis: Domestic resource mobilization remains inadequate, with only three African countries meeting the Abuja Declaration’s 15% health budget allocation target. Official development assistance (ODA) has declined by 70%, while reduced PEPFAR funding threatens treatment access for over 222,000 requiring daily treatment across seven high-burden countries. Health insurance coverage remains minimal, forcing up to 70% out-of-pocket health spending in some countries. Additionally, donor-driven vertical programs have fragmented health systems, while Africa produces only 3% of global pharmaceuticals despite bearing 23% of disease burden. These financing challenges extend beyond the HIV response, potentially causing 10.6 million additional tuberculosis cases and 2.2 million deaths during 2025–2030. Addressing this crisis requires coordinated action including strengthened domestic resource mobilization, innovative financing mechanisms, regional manufacturing capacity, and integrated health system governance. Urgent intervention is necessary to preserve decades of HIV prevention and treatment progress, particularly affecting the most vulnerable populations.